Comparação dos efeitos da fotobiomodulação a laser nos comprimentos de onda de 660 nm e 808 nm em queimaduras de espessura total em ratos: estudo pré clínico. - (:unkn) unknown (Universidade Brasil, 2024)
Burns are defined as thermal injuries that affect organic tissues, and can be classified in degree, according to their severity, with grade 3 burns being the most serious form of the injury. Concern regarding the rehabilitation of burn patients is related to recovery time and the severity of the injury's sequelae. Photobiomodulation therapy (TFBM) has gained prominence in the treatment of skin lesions, but the selection and application of parameters is still controversial. This study aims to evaluate the effects of TFBM using Red (660 nm) and Infrared (808 nm) laser on the quality of tissue regeneration in 3rd Degree burns in rats. Thirty male Wistar rats were used, randomly divided into 3 groups (n=10): control groups (C), with laser applied turned off, red laser group (GLV), treated only with TFBM using the 660 nm red laser and, infrared laser group (GLI), treated with 808 nm infrared laser. The animals were treated three times a week, for 21 days, totaling nine applications, using parameters suggested in the literature (ANDRADE, 2016). Photographic documentation was carried out on the first and last day of treatment to analyze wound contraction. On the 21st day, after the last treatment, the animals were euthanized, and tissue samples were collected for histological analyses.After the analyses, it was observed that the GIV, when compared to the GC and GV, showed an advanced phase of recovery and revascularization, with a thinner epidermis, minimal inflammatory infiltrate, and a well-established collagen organization throughout almost the entire dermis.
Keywords: Queimaduras; Fotobiomodulação; Laser vermelho; Laser infravermelho; Engenharia Biomédica (Bioengenharia)